The Effect Of Financial Ratios On Changes In Profit In Mining Companies Listed On The Indonesia Stock Exchange - Andreas W. P. Sinurat (TRIGIN PUBLISHER, 2021)
The purpose of this study was to determine the effect of the company's financial ratios are empirically, either partially or simultaneously to changes in earnings. Financial ratios tested is Current Ratio (CR), Working Capital to Total Assets (WCTA), Debt to Total Equity Ratio (DER), and Profit Margin (PM). This research is a kind of replication, causal research to previous research with the study population is a mining company listed on the Indonesia Stock Exchange during the period of 2007-2011. The sample selection method and purposive sampling of 31 companies listed in Indonesia Stock Securities acquired 11 companies sampled. The data used are secondary data. This study analyzes the relationship between CR, WCTA, DER, PM and changes in earnings. The statistical method used was multiple linear regression and performed classical assumption first. These results indicate that the variables CR, WCTA, DER, and PM simultaneously significant effect on changes in earnings. Partial test shows that the variables CR, WCTA and PM significant impact on earnings changes. Other variables that DER no significant effect on changes in earnings.